The reduced cost of providing a nationally recognised service for familial hypercholesterolaemia. Issue 1 (12th August 2014) - Pears, Robert; Griffin, Michael; Watson, Melanie; Wheeler, Rebecca; Hilder, Debbie; Meeson, Beverley; Bacon, Sallie; Byrne, Christopher D
Abstract : Objective: Familial hypercholesterolaemia (FH) affects 1 in 500 people in the UK population and is associated with premature morbidity and mortality from coronary heart disease. In 2008, National Institute for Health and Care Excellence (NICE) recommended genetic testing of potential FH index cases and cascade testing of their relatives. Commissioners have been slow to respond although there is strong evidence of cost and clinical effectiveness. Our study quantifies the recent reduced cost of providing a FH service using generic atorvastatin and compares NICE costing estimates with three suggested alternative models of care (a specialist-led service, a dual model service where general practitioners (GPs) can access specialist advice, and a GP-led service). Methods: Revision of existing 3 year costing template provided by NICE for FH services, and prediction of costs for running a programme over 10 years. Costs were modelled for the first population-based FH service in England which covers Southampton, Hampshire, Isle of Wight and Portsmouth (SHIP). Population 1.95 million. Results: With expiry of the Lipitor (Pfizer atorvastatin) patent the cost of providing a 10-year FH service in SHIP reduces by 42.5% (£4.88 million on patent vs £2.80 million off patent). Further cost reductions are possible as a result of the reduced cost of DNA testing, more management in general practice, and lower referral rates to specialists. For instance a dual-care model with GP management of patients supported by specialist advice when required, costs £1.89 million. Conclusions: The three alternative models of care are now <50% of the cost of the original estimates undertaken by NICE.